Rewiring FadR regulon for the selective production of omega-hydroxy palmitic acid from glucose in Escherichia coli - Kim, Joonwon; Yoo, Hee-Wang; Kim, Minsuk; Kim, Eun-Jung; Sung, Changmin; Lee, Pyung-Gang; Park, Beom Gi; Kim, Byung-Gee (Academic Press, 2018)
omega-Hydroxy palmitic acid (omega-HPA) is a valuable compound for an ingredient of artificially synthesized ceramides and an additive for lubricants and adhesives. Production of such a fatty acid derivative is limited by chemical catalysis, but plausible by biocatalysis. However, its low productivity issue, including formations of unsaturated fatty acid (UFA) byproducts in host cells, remains as a hurdle toward industrial biological processes. In this study, to achieve selective and high-level production of omega-HPA from glucose in Escherichia coil, FadR, a native transcriptional regulator of fatty acid metabolism, and its regulon were engineered. First, FadR was co-expressed with a thioesterase with a specificity toward palmitic acid production to enhance palmitic acid production yield, but a considerable quantity of UFAs was also produced. In order to avoid the UFA production caused by fadR overexpression, FadR regulon was rewired by i) mutating FadR consensus binding sites of fabA or fabB, ii) integrating fabZ into fabI operon, and iii) enhancing the strength of fabI promoter. This approach led to dramatic increases in both proportion (48.3-83.0%) and titer (377.8 mg/L to 675.8 mg/L) of palmitic acid, mainly due to the decrease in UFA synthesis. Introducing a fatty acid omega-hydroxylase, CYP153A35, into the engineered strain resulted in a highly selective production of omega-HPA (83.5 mg/L) accounting for 87.5% of total omega-hydroxy fatty acids. Furthermore, strategies, such as i) enhancement in CYP153A35 activity, ii) expression of a fatty acid transporter, iii) supplementation of triton X-100, and iv) separation of the omega-HPA synthetic pathway into two strains for a co-culture system, were applied and resulted in 401.0 mg/L of omega-HPA production. For such selective productions of palmitic acid and omega-HPA, the rewiring of FadR regulation in E. coil is a promising strategy to develop an industrial process with economical downstream processing.